Pro- and Anti-Angiogenic Factors: Their Relevance in Diabetic Foot Syndrome—A Review. (April 2022) - Schönborn, Martyna; Łączak, Patrycja; Pasieka, Paweł; Borys, Sebastian; Płotek, Anna; Maga, Paweł
Peripheral arterial disease can involve tissue loss in up to 50% of patients with diabetic foot syndrome (DFS). Consequently, revascularization of narrowed or occluded arteries is one of the most common forms of comprehensive treatment. However, technically successful angioplasty does not always result in the healing of ulcers. The pathomechanism of this phenomenon is still not fully understood, but inadequate angiogenesis in tissue repair may play an essential role. Changes in pro- and anti-angiogenic factors among patients with DFS are not always clear and conclusive. In particular, some studies underline the role of decreased concentration of pro-angiogenic factors and higher levels of anti-angiogenic mediators. Nevertheless, there are still controversial issues, including the paradox of impaired wound healing despite high concentrations of some pro-angiogenic factors, dynamics of their expression during the healing process, and their mutual relationships. Exploring this process among diabetic patients may provide new insight into well-known methods of treatment and show their real benefits and chances for improving outcomes.